Clinical evaluation of the national hospital‐acquired complication programme. Issue 11 (21st June 2022) - Duke, Graeme J.; Loughnan, Daniel; De Frietas, Maria; De Bont, Eliza; Braude, David; Liu, Rui; Hirth, Steven; Roodenburg, Owen; Newnham, Evan; Dārziņš, Peteris; McMahon, Lawrence P.
Abstract: Background: The national hospital‐acquired complication programme captures complications arising from patient‐related and hospital‐related factors, but the proportion of the two is unclear. Aim: Health services are encouraged to evaluate data from the national hospital‐acquired complications (HAC) programme and identify strategies to mitigate them. Methods: A retrospective chart review compared HAC extracted from administrative data. The setting was a 430‐bed university‐affiliated metropolitan hospital. Records from 260 participants with, and 462 without, reported HAC from 2619 multi‐day stay adults were reviewed. The main outcome measures were prevalence and positive predictive value (PPV) of HAC methodology. Results: No errors of HAC coding or classification were identified. Four hundred and twenty‐three HAC events were reported in 260 records; most commonly delirium ( n = 57; 13.4%), pneumonia ( n = 46; 10.9%), blood stream infection ( n = 39; 9.2%), hypoglycaemia ( n = 33; 7.8%) and cardiac arrhythmias ( n = 33; 7.8%). One hundred and eight (25.5%) 'HAC' events in 69 separations (95% confidence interval (CI) = 2.05–3.33 per 100 separations) were false positive, and 43 of 462 (95% CI = 6.72–12.22 per 100 separations) were false negative. Prevalence of total (reported plus missing) HAC was 16.06 (95% CI = 14.02–19.52), reported HAC was 9.93 (95% CI = 8.76–11.21), potentially preventable HAC was 1.68 (95% CI = 1.22–2.26) and healthcare errors was 0.31 (95% CI = 0.13–1.30) per 100 separations. PPV of HAC for true clinical events was 0.74 (0.68–0.79), preventable events 0.18 (0.13–0.23) and healthcare error 0.03 (0.01–0.06). Conclusions: Prevalence of HAC events was higher than expected, but PPV for healthcare errors was low, suggesting provision of care is a less common cause of HAC events than patient factors. HAC may be an indicator of hospital admission complexity rather than HAC.